MOFs and their derivatives as Sn-based anode materials for lithium/sodium ion batteries. Issue 48 (6th December 2021) - Liu, Kaiyuan; Li, Chao; Yan, Lijing; Fan, Meiqiang; Wu, Yechao; Meng, Xianhe; Ma, Tingli
Abstract : The increasing research of Sn-MOFs and Sn-based MOF-derivatives opens new avenues in promising anode materials for lithium/sodium ion batteries. Abstract : The rapid development of electric vehicles and consumer electronics places higher demands on the performance of secondary batteries. Tin-based materials are expected to be a commercial anode material candidate of next-generation rechargeable batteries due to their high gravimetric/volumetric capacity. However, tin anodes have large volume changes during charge–discharge cycles which leads to a rapid capacity decay. Emerging tin-based metal–organic frameworks (Sn-MOFs) have recently attracted the attention of researchers. Their characteristics of tunable porosity, huge surface areas and multiple active sites offer a wide range of possibilities for Li/Na ion storage and transport, and the coordination bonds stabilize the Sn atoms to the organic matrix buffering pulverization and aggregation. Besides, MOF-related Sn derivatives could also have novel diverse functional structures and achieve high-rate capacity and excellent cycle stability. In this review, we mainly summarize the structural features, energy storage mechanism, and recent advances in the rational design and preparation of Sn-MOFs and MOF-derived Sn-based composites for LiB and SIB anodes, and current challenges and future directions for further development are discussed.